Роль викладача в системі дистанційного навчання - Кухаренко, Володимир Миколайович; Рибалко, Олена Володимирівна; Твердохлєбова, Наталя Євгеніївна (Украинская ассоциация дистанционного образования, 2004)
The article contains information about the tutor’s influence on process of mastering of the knowledge by students in distant training. The levels of tutor’s productive activity are allocated. Besides we have discussed the peculiarities of tutor’s activity while teaching in the distant course.
Keywords: дистанційні курси; дистанційне навчання; електронне навчання; викладач-тьютор; педагогічні технології